Consistent Changes in Cortico-Subthalamic Directed Connectivity Are Associated With the Induction of Parkinsonism in a Chronically Recorded Non-human Primate Model - Bore, Joyce Chelangat; Toth, Carmen; Campbell, Brett A.; Cho, Hanbin; Pucci, Francesco; Hogue, Olivia; Machado, Andre G.; Baker, Kenneth B. (Frontiers in Neuroscience, 2022)
Parkinson’s Disease is a neurological disease with cardinal motor signs including bradykinesia and tremor. Although beta-band hypersynchrony in the cortico-basal ganglia network is thought to contribute to disease manifestation, resulting effects on network connectivity are unclear. We examined local field potentials from a non-human primate across the naïve, mild, and moderate disease states (model was asymmetric, left-hemispheric dominant) and probed cortico-cortical and cortico-subthalamic connectivity using Granger causality, a measure of directed effective connectivity, and a subsequent graph-theoretic analysis. Our network included the left subthalamic nucleus (L-STN), bilateral primary motor cortices (L-M1, R-M1) and bilateral premotor cortices (L-PMC, R-PMC). Results showed two distinct Granger causality peaks (Peak A at 5-20 Hz, Peak B at 25-45 Hz). Increases in Peak B connectivity and decreases in Peak A connectivity were associated with disease. Induction of mild disease was associated with several changes in connectivity: 1) the cortico-subthalamic connectivity in the descending direction (L-PMC to L-STN) decreased in the Peak A range while the reciprocal, ascending connectivity (L-STN to L-PMC) increased in the Peak B range; this may play a role in generating beta-band hypersynchrony in the cortex, 2) both L-M1 to L-PMC and R-M1 to R-PMC causalities increased, which may either be compensatory or a pathologic effect of disease, and 3) a decrease in connectivity occurred from the R-PMC to R-M1. The only significant change seen between mild and moderate disease was increased right cortical connectivity, which may reflect compensation for the left-hemispheric dominant moderate disease state. Graph-theory analysis suggested that the network became more “efficient”, or synchronized at both local and global levels, which agrees with our findings of increased beta-band connectivity.